2003
DOI: 10.4049/jimmunol.171.9.4680
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Adult Human B Cell Responses to Rotavirus Share Common Immunodominant Variable Gene Repertoires

Abstract: Ab repertoires exhibit marked restrictions during fetal life characterized by biases of variable gene usage and lack of junctional diversity. We tested the hypothesis that Ab repertoire restriction contributes to the observed poor quality of specific Ab responses made by infants to viral infections. We analyzed the molecular determinants of B cell responses in humans to two Ags of rotavirus (RV), a common and clinically important infection of human infants. We sequenced Ab H and L chain V region genes (VH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 37 publications
6
81
0
1
Order By: Relevance
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We found that the proportion of RV VP6-specific B cells that are memory cells represents a lower frequency and a less frequently isotype-switch phenotype compared with the proportion of randomly selected B cells that are memory cells. This high proportion of naive B cells in virus-specific clones in the circulation during infection, even in adults who likely have a history of many previous RV infections, is curious and unexplained (14,15,17). We showed previously a high frequency of naive B cells in the VP6 repertoire in adults, and a reduced frequency of somatic mutations in VP6-specific IgD Ϫ memory B cells (15,17).…”
Section: Discussionmentioning
confidence: 89%
“…The dominance of this V H gene segment appears to stem from the fact that the HCDR1 and HCDR2 loops specified by V H 1-46 exhibit an optimal Ab-combining site for loops on the surface of VP6 with a high level of shape complementarity and resulting optimal affinity for a primary response (26). Our original report on RV-specific B cell repertoire also suggested V H 1-46 gene usage in B cells sorted to be VP7 specific (15). Our subsequent studies, however, suggested that these clones were VP6 specific and likely sorted by the DLPs displaying VP6 that resulted from the loss of VP7 on the relatively unstable triple-layered particles used for sorting.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…36 Human fetal B cells have reduced antibody repertoires due to reduced junctional diversity; however, this is not a limiting determinant of the quality of antibody response to viruses of infants beyond the neonatal period. 37 It has also been observed that white blood cells from preterm and term neonates show blunted IL-10 and TGFb production after lipopolysaccharide and phorbol myristoyl aceate/ionomycin stimulation, respectively. Furthermore, IL-10 was less effective in inhibiting IL1a, IL-6, IL-8 and TNFa produced in response to LPS.…”
Section: Adaptive Immunitymentioning
confidence: 98%